2023
DOI: 10.33603/jka.v7i1.8454
|View full text |Cite
|
Sign up to set email alerts
|

Digital Literacy and The Changing Landscape of The Accounting Profession: The Role of Technology Adoption Model

Abstract: The aim of this research is to find out the current changes in the accounting professional landscape,that is the digitization of the accounting profession and the importance of digital literacy to deal with it, and how the technology adoption model mediates this relationship. Auditors at the Public Accounting Firm (KAP) Central Java Indonesia became the object of this study, a total of 21 Public Accounting Firms. This study uses purposive sampling method with sampling criteria respondents having work experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Moreover, the bad sentiment of digitalization occur as reduced profit will also affect market value and lower the BVPS. On the other hand, Ifada & Komara (2023) found that the adoption of technology significantly affect the accounting profession. Thus, when the accountant is not ready to face this technology changes, it will result on inefficient cost operation.…”
Section: Hypothesismentioning
confidence: 99%
“…Moreover, the bad sentiment of digitalization occur as reduced profit will also affect market value and lower the BVPS. On the other hand, Ifada & Komara (2023) found that the adoption of technology significantly affect the accounting profession. Thus, when the accountant is not ready to face this technology changes, it will result on inefficient cost operation.…”
Section: Hypothesismentioning
confidence: 99%